2013
DOI: 10.1073/pnas.1217420110
|View full text |Cite
|
Sign up to set email alerts
|

Neisseria infection of rhesus macaques as a model to study colonization, transmission, persistence, and horizontal gene transfer

Abstract: The strict tropism of many pathogens for man hampers the development of animal models that recapitulate important microbehost interactions. We developed a rhesus macaque model for studying Neisseria-host interactions using Neisseria species indigenous to the animal. We report that Neisseria are common inhabitants of the rhesus macaque. Neisseria isolated from the rhesus macaque recolonize animals after laboratory passage, persist in the animals for at least 72 d, and are transmitted between animals. Neisseria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 37 publications
0
27
0
1
Order By: Relevance
“…A recent study found that rhesus macaques can be colonized naturally by Neisseria species and demonstrated the feasibility of using the macaque model to investigate colonization and transmission of the organism (30). The results of the present study indicate that the macaque model also has the potential for investigation of the effects of FH binding on the immunogenicity and safety of meningococcal FHbp vaccines.…”
Section: Discussionmentioning
confidence: 61%
“…A recent study found that rhesus macaques can be colonized naturally by Neisseria species and demonstrated the feasibility of using the macaque model to investigate colonization and transmission of the organism (30). The results of the present study indicate that the macaque model also has the potential for investigation of the effects of FH binding on the immunogenicity and safety of meningococcal FHbp vaccines.…”
Section: Discussionmentioning
confidence: 61%
“…The habitats of commensal Neisseria in mammals are similar to those in humans, probably due to the shared anatomical and physiological features. For example in non-human primates, the oral and nasopharyngeal microbiome has been most extensively studied in the rhesus macaque (Macaca mulatta) given its potential as an animal model for human-specific pathogens such as N. meningitidis (Weyand et al, 2013). Although Neisseria species were identified in all rhesus macaque studies, their prevalence appeared to be lower than that in humans.…”
Section: Identification Of Neisseria Species In Non-human Mammalian Hmentioning
confidence: 98%
“…Due to the absence of bacteremia, it was suggested that N. meningitidis may travel from the nasal cavity to the meninges and subarachnoid space via the olfactory nerves (324). In rhesus macaques, commensal neisseria bacteria (RM Neisseria) were shown to be transmitted between animals and naturally colonized the epithelium covering the cribriform plate (336), suggesting that migration of neisseria bacteria along the olfactory pathway is not a phenomenon that is observed only in animals experimentally inoculated with pathogenic N. meningitidis. In the African "meningitis belt," the onset of meningococcal meningitis epidemics coincides with harsh, dry harmattan winds.…”
Section: Pathogens That Enter the Brain Through The Nose Bacteriamentioning
confidence: 99%